2018
DOI: 10.1021/acsaem.8b00898
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Synthesis by Radio Frequency Plasma Catalysis: Revealing the Underlying Mechanisms

Abstract: Nonthermal plasma is a promising alternative for ammonia synthesis at gentle conditions. Metal meshes of Fe, Cu, Pd, Ag, and Au were employed as catalysts in radio frequency plasma for ammonia synthesis. The energy yield for all these transition metal catalysts ranged between 0.12 and 0.19 g-NH 3 /kWh at 300 W and, thus, needs further improvement. In addition, a semimetal, pure gallium, was used for the first time as catalyst for ammonia synthesis, with energy yield of 0.22 g-NH 3 /kWh and with a maximum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
294
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(309 citation statements)
references
References 80 publications
13
294
2
Order By: Relevance
“…Table S4 summarizes the binding energies for atomic N, atomic H, NH, NH 2 and NH 3 species on different metals. Some of these metals have also been experimentally tested in an earlier work . The standard deviation for the reported yields was less than 5 % for all cases.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Table S4 summarizes the binding energies for atomic N, atomic H, NH, NH 2 and NH 3 species on different metals. Some of these metals have also been experimentally tested in an earlier work . The standard deviation for the reported yields was less than 5 % for all cases.…”
Section: Resultsmentioning
confidence: 98%
“…Several hypotheses have been proposed in relation to ammonia formation mechanisms in a plasma‐catalyst system, suggesting key differences with thermal catalysis and providing clues on what factors could be key to optimize the catalyst under plasma conditions. For example, Schneider and coworkers postulated in their work with atmospheric DBD plasma and supported transition metals that the kinetically relevant nitrogen source was vibrationally excited N 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[67,79] Based on this, Shah further demonstrated that the electron temperature is the main factor controlling N 2 dissociation in the gas phase. Although in their studies the metal-woolc atalysts wereu sed, they came to the same conclusions as Shah et al [77] that Au was the most effective catalyst under both atmospheric and low pressures ( Figure 5). under atmospheric dielectric barrier discharge conditions.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 56%
“…[76][77][78] In addition to exploring the effects of the above-mentionedc atalysts, the authors also discussed the mechanisms of the fundamentaln onthermalp lasma-assisted ammonia synthesis based on ap roposal by Carrasco et al, [79] who stated that the plasma-assisted ammonia synthesis under vacuum occurs mainly through the ER and Langmuir-Hinshelwood (LH) mechanisms (they described the interactions between surface-adsorbed and gasphase speciesa nd the interactions betweent wo surface-adsorbed species, respectively). [77] Iwamoto et al [80] and Aihara et al [81] also compared the catalytic activities of different single-metal catalysts (Fe, Cu, Pd, Ag, etc.) [77] Iwamoto et al [80] and Aihara et al [81] also compared the catalytic activities of different single-metal catalysts (Fe, Cu, Pd, Ag, etc.)…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%